Empirical Analysis Of The Artworks From Two Selected Photographers In Malaysia - Munusamy, Ravindran (2020)
The research focused on empirical analysis of the artworks from two selected finest artist-photographers, Soraya Yusof Talismail and Patrick Low. In the field of photography, very few passionate photographers who have produced marvellous images of Malaysia which were under-appreciated in the world of Art. (Subhadra Devan, 2013).